Podocyte Lysosome Dysfunction in Chronic Glomerular Diseases - Li, Guangbi (Int J Mol Sci, 2020)
Podocytes are visceral epithelial cells covering the outer surface of glomerular capillaries in the kidney. Blood is filtered through the slit diaphragm of podocytes to form urine. The functional and structural integrity of podocytes is essential for the normal function of the kidney. As a membrane-bound organelle, lysosomes are responsible for the degradation of molecules via hydrolytic enzymes. In addition to its degradative properties, recent studies have revealed that lysosomes may serve as a platform mediating cellular signaling in different types of cells. In the last decade, increasing evidence has revealed that the normal function of the lysosome is important for the maintenance of podocyte homeostasis. Podocytes have no ability to proliferate under most pathological conditions; therefore, lysosome-dependent autophagic flux is critical for podocyte survival. In addition, new insights into the pathogenic role of lysosome and associated signaling in podocyte injury and chronic kidney disease have recently emerged. Targeting lysosomal functions or signaling pathways are considered potential therapeutic strategies for some chronic glomerular diseases. This review briefly summarizes current evidence demonstrating the regulation of lysosomal function and signaling mechanisms as well as the canonical and noncanonical roles of podocyte lysosome dysfunction in the development of chronic glomerular diseases and associated therapeutic strategies.